1993
DOI: 10.1159/000266265
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Articulatory Movements of Speech in a Group of First-Graders

Abstract: Associations between different types of misarticulations and morphology as well as function of the speech articulators were assessed in 287 first-grade children. Sounds produced too far anteriorly evidently were due to immaturity of the articulatory speech movements, which showed a tendency to improve spontaneously with age. Sounds produced too far posteriorly correlated positively with problems in coordinating the movements of different muscles of the tongue, indicating a possible dyspractic origin. Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
(16 reference statements)
2
12
0
1
Order By: Relevance
“…Ten-year-old boys in the hospital referral group had more difficulties in almost all tasks related to the coordination of tongue movements than girls of the same age did. During the first phase of the study, boys had more /r/ disorders pro duced too far posteriorly, which seemed to be resistant to treatment [18] and were associat ed with difficulties in coordinating the move ments of the muscles of the tongue [35], Ac cording to the present results, the frequency of posterior variants among 10-year-old boys continued to be high. Evidently slower motor maturation alone does not explain the relative delay in the motor coordination development of boys with posterior misarticulalions.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Ten-year-old boys in the hospital referral group had more difficulties in almost all tasks related to the coordination of tongue movements than girls of the same age did. During the first phase of the study, boys had more /r/ disorders pro duced too far posteriorly, which seemed to be resistant to treatment [18] and were associat ed with difficulties in coordinating the move ments of the muscles of the tongue [35], Ac cording to the present results, the frequency of posterior variants among 10-year-old boys continued to be high. Evidently slower motor maturation alone does not explain the relative delay in the motor coordination development of boys with posterior misarticulalions.…”
Section: Discussionsupporting
confidence: 78%
“…The morphology and function of the articulators were recorded for all subjects by an experienced phoniatrician using the method developed for diagnos tics at the Department of Otolaryngology and Phoniatrics, Kuopio University Hospital (Appendix I) [35]. 194 Qvamstrom/Jaroma/Lainc Changes in Oral Motoricsof Schoolchildren The tonus of the lips, the width and length of the tongue and the length of the soft palate were assessed visually.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early development and especially early speech development as well as early progress of fine motor movements have been reported to be slower among boys [4,19,[20][21][22]. Misarticulating boys seem to have more inaccurate tongue movements and problems in coordinating those movements than children without speech defects [23]. Disorders in speech sound production in general seem to reflect immaturity in fine motor control of the orofacial muscles in 6-to 8-year-old children [24].…”
Section: Discussionmentioning
confidence: 99%
“…(p. 155) A review of the studies since Winitz concluded that there is still no definitive answer to this question. Studies that treated this population as a single undifferentiated group (e.g., Dworkin & Culatta, 1985;Jordan, Hardy, & Morris, 1978;Qvarnstrom, Jaroma, & Laine, 1993) found both differences and no differences compared to typically developing children. Studies that compared subgroups of children with SD of unknown origin to each other or to typically developing children (e.g., Bradford & Dodd, 1996;Hamlet, 1985;Hetrick & Sommers, 1988;McGlone & Proffit, 1973) also revealed a mixed picture.…”
Section: The Speech-motor Deficit Hypothesismentioning
confidence: 99%